The mediation of the integrated approach to literacy instruction programme to grade eight learners in an independent secondary school in South Africa. - Andrews, Douglas Peter Spencer (My University, 2013)
The role of literacy skills in learning and the ability to have the cognitive learning skills necessary to receive, process and make meaning of information is core to academic achievement at school. Many learners whose underdeveloped literacy skills prove to be a considerable barrier to learning struggle to make any significant progress at school, particularly at secondary school if these learners have come into their grade eight year from a remedial primary school where only a limited curriculum is taught. Often these learners drop out of the educational system altogether with no real alternatives available to them. Inclusive education policy states that schools must do everything they can to make the curriculum accessible to all learners regardless of their barrier to learning. This research project examined the critical success factors of implementing a one-on-one mediated literacy programme to eight selected grade eight learners as part of their school programme. The learners selected to be participants on the programme were identified from an analysis of background history, educational testing, and parent and teacher recommendations as learners whose specific barrier to learning was associated with inadequate literacy skill ability. The programme was called the Integrated Approach to Literacy Instruction(IATLI), and it combined the mediation of literacy skills simultaneously with metacognitive learning strategies. The research project was participatory in nature, as the researcher was the mediator of the programme to the eight learners. The project was based on participatory action research theory, and was a case-study design implemented at an independent secondary school in Johannesburg. The methodology used to evaluate the research project was a mixed research design incorporating structured surveys of the teaching staff, pre- and post-testing of the eight learners using standardized educational tests that evaluated literacy ability, semi-structured interviews with the teachers who taught the eight learners, and commentary from the learners themselves recorded in the researcher’s journal. Quantitative and qualitative analysis of the data indicated that the programme was a worthwhile initiative, and that certain critical success factors of the IATLI programme’s implementation emerged. Of these critical success factors, highlighted in the research sub-questions, success was often more evident in some learners than others. The data also highlighted a number of challenges that the programme’s implementation exposed, notably sustainability of the programme in the long term, as the programme was driven by the learning support specialist and the factor of burnout with regard to the intensive nature of the programme and its demands on the learner participants and the school’s internal structures. Other challenges that emerged were the practical aspects of integrating an inclusive education initiative into the demanding high school curriculum, and addressing the paradigm shift necessary to get all educators collaborating with learning support programme outcomes and then supporting initiatives in their own teaching.
Keywords: Case-study; Cognitive; Comprehension; Curriculum; Inclusion; Learner; Literacy; Participant; Phonetics; Researcher; Self-esteem; Self-efficacy